Osteochondritis Dissecans of the Humeral Capitellum in Young Athletes: Comparison Between Baseball Players and Gymnasts. Issue 3 (1st March 2017) - Kajiyama, Shiro; Muroi, Satoshi; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Kawai, Nobuaki; Osaki, Makoto
Background: Osteochondritis dissecans (OCD) lesions are often observed in the humeral capitellum both in young baseball players and gymnasts. It is generally believed that capitellar OCD in baseball players can be seen on an anteroposterior (AP) radiograph with the elbow in 45° of flexion. However, the mechanism of injury seems to be different in baseball players and gymnasts. Repetitive valgus overload with the elbow in flexion is believed to be the cause of capitellar OCD lesions in baseball players, whereas weightbearing with the elbow in extension may be the cause of OCD in gymnasts. Purpose: To determine the difference in capitellar OCD location between baseball players and gymnasts and to propose the optimal AP radiographic angle of the elbow for visualization of early-stage OCD lesions in adolescent gymnasts. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Subjects consisted of 95 baseball players (95 elbows) and 21 gymnasts (24 elbows) with a mean age of 13.7 years (range, 11-18 years). To localize the lesion, inclination of the affected area in the humeral capitellum against the humeral axis was investigated using sagittal computed tomography images of the elbow. The inclination angle was defined as the angle between the long axis of the humerus and the line perpendicular to a line that connected the anterior and posterior margin of the lesion. The inclination angle in each group was compared and statistically analyzed. Results: The mean inclination angle was 57.6° ± 10.7° in baseball players and 28.0° ± 10.7° in gymnasts. Capitellar OCD lesions were located more anterior in baseball players when compared with gymnasts ( P < .01). Conclusion: Due to differences in applied stress, capitellar OCD lesions in baseball players were located more anteriorly compared with those seen in gymnasts. Therefore, although AP radiographs with the elbow in 45° of flexion are optimal for detecting OCD lesions in baseball players, radiographs with less elbow flexion or full extension are more useful in gymnasts, especially in early-stage OCD.